PENGENALAN BAHASA INGGRIS DASAR MELALUI MEDIA POSTER DAN PUZZLE BOARD - Muhammad Agus Hardiansyah; Septi Kurniasih; Mochamad Naim (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Indonesia English is the most widely spoken language in the world. Mastery of English is a very important ability to be able to communicate with the global world. The importance of introducing English as early as possible to students starts from introducing basic skills such as letters, numbers, and vocabulary. This English introductory activity uses posters and puzzle boards so that this activity can provide a pleasant experience for students at SDN Kertamukti 1 Sumur District, Pandeglang Regency. The activity which lasted for 2 meetings involved 24 students who were in class IV.